Top-down mechanisms of anesthetic-induced unconsciousness - Mashour, George A. (Frontiers in Systems Neuroscience, 2014)
The question of how structurally and pharmacologically diverse general anesthetics disrupt consciousness has persisted since the 19th century. There has traditionally been a significant focus on “bottom-up” mechanisms of anesthetic action, in terms of sensory processing, arousal systems and structural scales. However, recent evidence suggests that the neural mechanisms of anesthetic-induced unconsciousness may involve a “top-down” process, which parallels current perspectives on the neurobiology of conscious experience itself. This article considers various arguments for top-down mechanisms of anesthetic-induced unconsciousness, with a focus on sensory processing and sleep-wake networks. Furthermore, recent theoretical work is discussed to highlight the possibility that top-down explanations may be causally sufficient, even assuming critical bottom-up events.